2023
DOI: 10.1155/2023/6818524
|View full text |Cite
|
Sign up to set email alerts
|

circRNA_17725 Promotes Macrophage Polarization towards M2 by Targeting FAM46C to Alleviate Arthritis

Abstract: Accumulating studies have implicated that circular RNAs (circRNAs) play vital roles in the pathogenesis of rheumatoid arthritis (RA). Dysregulation of macrophage polarization leads to immune homeostatic imbalance in RA. However, the altering effects and mechanisms of circRNAs on macrophages polarization and immune homeostatic balance remain largely unclear. We aimed to investigate the potential role of circRNA_17725 in RA. The high-throughput sequence was performed to identify the dysregulated circRNAs in RA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…For example, Qiao et al [46] revealed that circRNA_0048211 could bind to miRNA-93-5p and was negatively correlated with miRNA-93-5p and positively correlated with BMP2 (BMP2 was a direct target of miRNA-93-5p), thus alleviating the progression of postmenopausal osteoporosis. Moreover, similar findings have been reported in breast cancer [47], diabetic nephropathy [48], osteoarthritis [49], cutaneous squamous cell carcinoma [50], and arthritis [51]. In parallel with these reports, our studies showed that hsa_-circ_0102678 expression was inversely correlated with miR-146a expression in acne, but this correlation was positive with IRAK1 and TRAF6, indicating that hsa_circ_0102678 might sponge miR-146a to regulate inflammation in acne.…”
Section: Discussionsupporting
confidence: 90%
“…For example, Qiao et al [46] revealed that circRNA_0048211 could bind to miRNA-93-5p and was negatively correlated with miRNA-93-5p and positively correlated with BMP2 (BMP2 was a direct target of miRNA-93-5p), thus alleviating the progression of postmenopausal osteoporosis. Moreover, similar findings have been reported in breast cancer [47], diabetic nephropathy [48], osteoarthritis [49], cutaneous squamous cell carcinoma [50], and arthritis [51]. In parallel with these reports, our studies showed that hsa_-circ_0102678 expression was inversely correlated with miR-146a expression in acne, but this correlation was positive with IRAK1 and TRAF6, indicating that hsa_circ_0102678 might sponge miR-146a to regulate inflammation in acne.…”
Section: Discussionsupporting
confidence: 90%
“…Currently, circRNA-based drugs have been identified to have enormous potential for clinical purposes (He et al, 2021). In RA, Yang et al (2023) showed cir-cRNA_17725 could alleviate bone destruction and joint injuries by inducing macrophage M2 polarization in arthritis mice. Additionally, ciRS-7 overexpression abolished miR-7-induced suppression of the hyperproliferation, invasion, and migration in RA-FLSs (Hu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, circRNAs are widely involved in many biological processes, such as cellular viability, metastasis and apoptosis 13,14 . Studies also show that circRNAs are associated with macrophage polarization in tumours 7,15 . For instance, hsa_circ_0074854 knockdown suppresses the migration and invasion of HCC cells via inhibiting exosome‐mediated macrophage M2 polarization 16 .…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Studies also show that circRNAs are associated with macrophage polarization in tumours. 7,15 For instance, hsa_circ_0074854 knockdown suppresses the migration and invasion of HCC cells via inhibiting exosome-mediated macrophage M2 polarization. 16 Hsa_circ_0010882 is located in chr: 24021149-24021281 and derives from the host gene RPL11.…”
mentioning
confidence: 99%